ANTI-CRISIS MEASURES OF ECONOMIC POLICY IN LITHUANIA AND IN OTHER BALTIC COUNTRIES - Davulis, Gediminas (European Scientific Journal, ESJ, 2013)
The article deals with the economic situation and the state economic policy in Lithuania before and during the crisis. The pre-crisis period, i.e. 2004-2007 years, were the years of the fast economic growth in Lithuanian and other Baltic countries economies, which were unprecedented in postwar Europe. The growth Lithuanian economy was interrupted by global economics and finance crises, which appeared in Lithuania in 2008 year. The macroeconomic situation of Lithuania, the main factors influenced to economy situation of country and means of government economy policy before and in the period of crisis using statistic date are discussed. The anti-crisis policy of other Baltic countries is presented in the article. The statistic data showed that economic processes were similar without essential differences in all Baltic countries with exception the spheres of public finances where Estonia had obvious advantage in comparison with Lithuania and Latvia.